A hybrid procedure to identify the optimal stiffness coefficients of elastically restrained beams - Silva, Tiago; Loja, Maria; Maia, Nuno; Barbosa, Joaquim (Zielona Góra: Uniwersytet Zielonogórski)
The formulation of a bending vibration problem of an elastically restrained Bernoulli?Euler beam carrying a finite number of concentrated elements along its length is presented. In this study, the authors exploit the application of the differential evolution optimization technique to identify the torsional stiffness properties of the elastic supports of a Bernoulli-Euler beam.
Keywords: transverse vibration; Bernoulli-Euler beam; elastic support; torsional stiffness coefficient; differential evolution; Kriging predictor